Carbon-coated current collector and preparation method and application thereof
Through the synergistic effect of polyacrylic polymers, polystyrene microspheres and crosslinking agents, a carbon-coated current collector is formed, which solves the problem of insufficient bonding strength between the current collector and the active material, and improves the electrochemical performance of lithium-ion batteries and The cycle life of the battery.
Patent Information
- Application Number
- CN202411366466.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-07
AI Technical Summary
The bonding strength between the current collector and the active material in existing lithium-ion batteries is insufficient, resulting in increased internal resistance of the battery, affecting cycle life and safety performance, and the roughness of conventional base foils and the limitation of adhesives make the electrode sheet coated. The difficulty of covering is very affecting battery performance.
The synergistic combination of polyacrylic polymers, polystyrene microspheres and crosslinking agents is adopted to form a coating current collector, improve the adhesion between the current collector and the electrode active material layer, and allow lithium ions through the spherical structure of the PS microspheres. Transmission, reduce interface resistance.
It significantly improves the electrochemical performance of the electrode plate, reduces the internal resistance of the battery, improves the first charge and discharge efficiency, and enhances the adhesion of the electrode plate and the cycling performance of the battery.
Smart Images

Figure BDA0005068518560000181 
Figure BDA0005068518560000191 
Figure BDA0005068518560000192
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a carbon-coated current collector and a preparation method and application thereof. Background Art
[0002] The current collector is an important component in lithium-ion batteries. It mainly carries active materials and conducts electrons to the external circuit. The peel strength between the current collector and the active materials and high conductivity are directly related to the electrochemical properties of lithium-ion batteries.
[0003] In the traditional lithium battery pole piece manufacturing process, the active material slurry is directly coated on the surface of the base foil current collector, and after drying, the active material is fixed on the surface of the base foil current collector by a binder, and then the positive and negative electrodes are prepared. However, conventional base foils have the following problems: ① The contact area between the conventional base foil metal current collector and the active material particles is limited, and the interface resistance is large; ② The bonding strength of the binder is limited. During the continuous charge and discharge process, it is easy for the active material and the current collector to expand and separate, resulting in further increase in the internal resistance of the battery, which affects the cycle life and safety performance of the battery; ③ Due to the processing technology of the foil material, the surface roughness of the conventional base foil metal current collector is limited, and the additive oil added during the rolling process is residual, resulting in a large interfacial tension, making it difficult to wet the electrode material coating, and there are leaks and uneven coating. The processing is difficult, which affects the battery's electrical performance.
[0004] At present, the current collector is often used as a simple carrier material in lithium-ion batteries, or the conductivity of the current collector is improved by coating a carbon layer. However, this method makes the current collector have a low conductivity or poor adhesion to the pole piece after coating the active material, which easily leads to the pole piece active material layer falling off. In addition, the powdering of the pole piece coating during the cycle process will also increase the contact resistance between the current collector and the active material, seriously affecting the cycle performance.
[0005] CN111430719A discloses a system and method for preparing a current collector microstructure based on a lithium battery pole piece. The current collector microstructure is processed on the current collector by controlling a laser ablation head. The current collector microstructure can increase the bonding area between the electrode material and the current collector and improve the adhesion between the electrode material and the current collector. However, the production cost of using a laser processing device is high.
[0006] CN111710871A discloses a conductive coating for a lithium ion battery current collector, a lithium ion battery current collector, a pole piece and a lithium ion battery. An active substance / carbon composite material is added to the coating to improve the adhesion between the coating and the current collector and reduce the contact resistance between the material and the current collector. However, when the active material is further coated on the current collector, there will also be an interface contact problem between the active material and the active substance / carbon composite material. Therefore, the contact resistance between the coating and the current collector needs to be further improved.
[0007] Therefore, how to improve the direct bonding strength between the current collector and the active material layer and improve the electrochemical performance of the electrode is currently worthy of study. Summary of the invention
[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a carbon-coated current collector and its preparation method and application. The carbon-coated current collector provided by the present invention improves the bonding force between the current collector and the electrode active material layer, reduces the interface resistance, and improves the electrochemical performance of the electrode sheet through the synergistic effect of polyacrylic acid polymer, polystyrene (PS) microspheres and cross-linking agent.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a carbon-coated current collector, comprising a current collector substrate and a carbon-coated layer on at least one side of the current collector substrate; the carbon-coated layer comprises a conductive agent, a binder and a cross-linking agent; the binder comprises a polyacrylic polymer and polystyrene microspheres.
[0011] The carbon-coated current collector provided by the present invention improves the bonding effect between the carbon-coated layer and the electrode active material layer through the action of a cross-linking agent between the polyacrylic acid polymer and the polystyrene (PS) microspheres. At the same time, the spherical structure of the PS allows normal transmission of lithium ions during battery operation, reduces the internal resistance of the battery, and greatly improves the initial charge and discharge efficiency of the battery. The two-dimensional bonding network structure formed by the polyacrylic acid polymer and the polystyrene microspheres through the action of the cross-linking agent is more compact, thereby better reducing the interface resistance.
[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0013] Preferably, the mass ratio of the conductive agent to the binder is 1:2 to 3:8.
[0014] Preferably, the mass ratio of the polyacrylic acid polymer, the polystyrene microspheres and the cross-linking agent is 100:(15-35):(1-4).
[0015] Preferably, the cross-linking agent includes any one of aziridine, polycarbodiimide or polyisocyanate, or a combination of at least two thereof.
[0016] Preferably, the ratio of the particle size D90 of the polystyrene microspheres to the molecular weight of the polystyrene microspheres is 0.0003125 to 0.00039, and the unit of D90 is μm.
[0017] Preferably, the particle size D90 of the polystyrene microspheres is 1 to 9 μm.
[0018] Preferably, the molecular weight of the polystyrene microspheres is 6,000-70,000.
[0019] In a second aspect, the present invention provides a method for preparing the carbon-coated current collector as described in the first aspect, the preparation method comprising the following steps:
[0020] Mixing a conductive agent, a binder, a cross-linking agent and a solvent to obtain a carbon-coated layer slurry, and applying the carbon-coated layer slurry to at least one side of the current collector substrate to obtain the carbon-coated current collector;
[0021] Wherein, the binder comprises polyacrylic acid polymer and polystyrene microspheres.
[0022] Preferably, after the coating is completed, the carbon-coated current collector is dried to obtain the carbon-coated current collector.
[0023] In a third aspect, the present invention provides an electrode plate, which includes the carbon-coated current collector as described in the first aspect and an electrode active material layer located on at least one side of the carbon-coated current collector; the electrode active material layer includes a positive electrode active material layer or a negative electrode active material layer.
[0024] In the present invention, the electrode sheet includes a positive electrode sheet (the electrode active material layer is a positive electrode active material layer) and / or a negative electrode sheet (the electrode active material layer is a negative electrode active material layer).
[0025] Preferably, the electrode active material layer is a negative electrode active material layer.
[0026] When the carbon-coated current collector provided by the present invention is used for a negative electrode plate and the active material of the negative electrode plate includes a silicon-based material (the silicon-based material includes but is not limited to nano-silicon material, silicon-carbon material and silicon-oxygen material, etc.), it not only improves the bonding effect, reduces the internal resistance, reduces the interface resistance and the initial charge and discharge efficiency, but also inhibits the volume expansion of the silicon-based negative electrode, thereby effectively improving the initial efficiency of the silicon-based negative electrode.
[0027] In a fourth aspect, the present invention further provides a battery, comprising the electrode plate as described in the third aspect.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The carbon-coated current collector provided by the present invention improves the bonding effect between the carbon-coated layer and the electrode active material layer through the action of a cross-linking agent between the polyacrylic acid polymer and the polystyrene (PS) microspheres. At the same time, the spherical structure of the PS allows normal transmission of lithium ions during battery operation, reduces the internal resistance of the battery, and greatly improves the initial charge and discharge efficiency of the battery. The two-dimensional bonding network structure formed by the polyacrylic acid polymer and the polystyrene microspheres through the action of the cross-linking agent is more compact, thereby better reducing the interface resistance. DETAILED DESCRIPTION
[0030] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0032] In a specific embodiment, the present invention provides a carbon-coated current collector, which includes a current collector substrate and a carbon-coated layer on at least one side of the current collector substrate; the carbon-coated layer includes a conductive agent, a binder and a cross-linking agent; the binder includes a polyacrylic polymer and polystyrene microspheres.
[0033] It should be noted that the polypropylene polymer in the present invention includes polymer types having branched polymers, including but not limited to at least one of polyacrylic acid (PAA) or polyvinyl alcohol (PVA).
[0034] The carbon-coated current collector provided by the present invention improves the bonding effect between the carbon-coated layer and the electrode active material layer through the action of a cross-linking agent between the polyacrylic acid polymer and the polystyrene (PS) microspheres. At the same time, the spherical structure of the PS allows normal transmission of lithium ions during battery operation, reduces the internal resistance of the battery, and greatly improves the initial charge and discharge efficiency of the battery. The two-dimensional bonding network structure formed by the polyacrylic acid polymer and the polystyrene microspheres through the action of the cross-linking agent is more compact, thereby better reducing the interface resistance.
[0035] In the present invention, the polyacrylic acid polymer and polystyrene microspheres in the binder are indispensable, and the polystyrene must be in a microsphere structure to simultaneously achieve the technical effects of improving the bonding effect and improving the initial charge and discharge efficiency; if the polyacrylic acid polymer is not added to the binder, the coating effect of the polystyrene microspheres is extremely poor and cannot be completely and evenly coated on the surface of the current collector; and if the polystyrene microspheres are not contained, not only the bonding effect cannot be improved, but also the effect of improving the initial charge and discharge efficiency of the battery cannot be achieved; even if the polystyrene polymer is present, but it is not in a microsphere shape, the problem of large internal resistance of the battery cannot be solved; similarly, if there is no cross-linking agent, the synergistic effect will be greatly reduced, resulting in a loose bonding network, and the effects of improving bonding strength and reducing internal resistance cannot be guaranteed.
[0036] As a preferred technical solution in a specific implementation, the mass ratio of the conductive agent to the binder is 1:2 to 3:8, for example 1:2, 3:6.5, 3:7, 3:7.5 or 3:8, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] As a preferred technical solution in a specific embodiment, the mass ratio of the polyacrylic acid polymer, the polystyrene microspheres and the cross-linking agent is 100:(15-35):(1-4), for example, 100:15:1, 100:15:2, 100:15:4, 100:25:1, 100:25:2, 100:25:3, 100:25:4, 100:30:1, 100:30:2 or 100:30:4, 100:35:1, 100:35:2, 100:35:3 or 100:35:4, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In the present invention, by further adjusting the mass ratio of the polyacrylic acid polymer, the polystyrene microspheres and the cross-linking agent to 100:(15-35):(1-4), the stability of the bonding network structure in the slurry can be better achieved. When used at the battery end, the bonding between the coating and the positive and negative electrodes can be enhanced; and the stable arrangement of the polystyrene microspheres can also better reduce the internal resistance of the battery.
[0039] As a preferred technical solution in a specific embodiment, the cross-linking agent includes any one of aziridine, polycarbodiimide or polyisocyanate, or a combination of at least two of them.
[0040] As a preferred technical solution in a specific embodiment, the ratio of the particle size D90 of the polystyrene microspheres to the molecular weight of the polystyrene microspheres is 1 / 70000 to 9 / 6000, for example 1 / 70000, 5 / 50000, 9 / 6000, etc. The unit of D90 is μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] It should be noted that the ratio of the particle size D90 of the polystyrene microspheres to the molecular weight of the polystyrene microspheres in the present invention is a purely numerical ratio result.
[0042] In the present invention, the ratio of the particle size D90 of the polystyrene microspheres to the molecular weight of the polystyrene microspheres is a pure numerical value. By regulating the relationship between the particle size D90 and the molecular weight, it is more conducive to improving the bonding effect between the carbon-coated current collector and the electrode active material layer, and can better reduce the internal resistance, reduce the interface resistance, and improve the initial charge and discharge efficiency of the battery.
[0043] As a preferred technical solution in a specific embodiment, the particle size D90 of the polystyrene microspheres is 1 to 9 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 9 μm, 7 μm, 8 μm or 9 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] As a preferred technical solution in a specific embodiment, the molecular weight of the polystyrene microspheres is 6000-70000, for example 6000, 6300, 6500, 7000, 8000, 9000, 10000, 12800, 15000, 20000, 25000, 30000, 35000, 40000, 45000, 50000, 55000, 60000, 65000 or 70000, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In the present invention, after further adjusting the particle size D90 of the polystyrene microspheres to 1-9 μm and the molecular weight of the polystyrene microspheres to 6000-70000, the internal resistance is reduced to the maximum extent, and the initial charge and discharge efficiency of the battery end is improved; at the same time, the bonding effect of the carbon coating layer is more excellent.
[0046] In another specific embodiment, the present invention provides a method for preparing a carbon-coated current collector as described in the above specific implementation method, the preparation method comprising the following steps:
[0047] Mixing a conductive agent, a binder, a cross-linking agent and a solvent to obtain a carbon-coated layer slurry, and applying the carbon-coated layer slurry to at least one side of the current collector substrate to obtain the carbon-coated current collector;
[0048] Wherein, the binder comprises polyacrylic acid polymer and polystyrene microspheres.
[0049] As another preferred technical solution in another specific embodiment, after the coating is completed, the carbon-coated current collector is dried to obtain the carbon-coated current collector.
[0050] It should be noted that the specific types of the conductive agent, solvent and current collector substrate provided by the present invention, the solid content of the carbon coating slurry, the coating method, the coating surface density and the drying method, etc., are all conventional technical choices, and those skilled in the art can make adaptive choices and adjustments according to actual needs;
[0051] Optionally, the conductive agent includes but is not limited to any one of conductive carbon black, conductive graphite, carbon nanotubes, carbon nanofibers, graphene or MXene materials, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of conductive carbon black and conductive graphite, a combination of conductive graphite and carbon nanotubes, a combination of carbon nanotubes and carbon nanofibers, a combination of carbon nanofibers and graphene, a combination of conductive carbon black and MXene materials, etc.;
[0052] Optionally, the solvent includes but is not limited to water;
[0053] Optionally, the current collector substrate includes but is not limited to copper foil, aluminum foil, stainless steel strip, plastic film or fabric, etc.;
[0054] Optionally, the solid content of the carbon coating layer slurry may be 8% to 15%, for example 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0055] Optionally, the surface density of the single-sided coating in the carbon coating layer can be 0.3 to 1.5 g / m 2 , for example 0.3g / m 2 , 0.4g / m 2 , 0.5g / m 2 , 0.6g / m 2 , 0.7g / m 2 , 0.8g / m 2 , 0.9g / m 2 , 1.0g / m 2 , 1.1g / m 2 , 1.2g / m 2 , 1.3g / m 2 , 1.4g / m 2 or 1.5g / m 2 The above range is not limited to the listed values, and other values not listed within the above range are also applicable.
[0056] In one embodiment, the present invention provides an electrode plate, which includes a carbon-coated current collector as described in the above specific embodiment and an electrode active material layer located on at least one side of the carbon-coated current collector; the electrode active material layer includes a positive electrode active material layer or a negative electrode active material layer.
[0057] In the present invention, the electrode sheet includes a positive electrode sheet (the electrode active material layer is a positive electrode active material layer) and / or a negative electrode sheet (the electrode active material layer is a negative electrode active material layer).
[0058] Preferably, the electrode active material layer is a negative electrode active material layer.
[0059] When the carbon-coated current collector provided by the present invention is used for a negative electrode plate and the active material of the negative electrode plate includes a silicon-based material (the silicon-based material includes but is not limited to nano-silicon material, silicon-carbon material and silicon-oxygen material, etc.), it not only improves the bonding effect, reduces the internal resistance, reduces the interface resistance and the initial charge and discharge efficiency, but also inhibits the volume expansion of the silicon-based negative electrode, thereby effectively improving the initial efficiency of the silicon-based negative electrode.
[0060] In one application embodiment, the present invention further provides a battery, which includes the electrode plate described in the above embodiment.
[0061] It is understandable that, except for the above-mentioned limitations on the carbon-coated current collector and electrode plates, the rest of the preparation materials and methods of the battery provided by the present invention are selected according to conventional techniques, and those skilled in the art can select and adjust them according to actual needs.
[0062] The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator (if a solid electrolyte is used, the separator may not be included) and an electrolyte.
[0063] Optionally, the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer covering the surface of the positive electrode current collector, and the positive electrode current collector can be the carbon-coated current collector provided in the first aspect;
[0064] The positive electrode active material layer may include a positive electrode active material;
[0065] Specifically, the positive electrode active material is a compound capable of reversibly inserting and extracting lithium, and specifically, may include a lithium transition metal composite oxide containing lithium and at least one transition metal selected from the group consisting of nickel, cobalt, manganese and aluminum; further, may include lithium and a transition metal such as nickel, cobalt or manganese;
[0066] In addition to the positive electrode active material, the positive electrode active material layer may further include a positive electrode binder and / or a positive electrode conductive material;
[0067] The positive electrode binder is used to bind the active material, the conductive material and the current collector together, and may include at least one selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, styrene-butadiene rubber and fluororubber, preferably polyvinylidene fluoride;
[0068] The conductive material is mainly used to assist and improve the conductivity in the secondary battery, and there is no particular limitation as long as it has conductivity without causing chemical changes. The conductive material may include graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; metal powders, such as fluorocarbon powders, aluminum powders and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives, and from the aspect of improving conductivity, carbon black may be preferably included.
[0069] The positive electrode may be manufactured by coating a positive electrode slurry including a positive electrode active material and optionally a positive electrode binder, a positive electrode conductive material, and a solvent for forming a positive electrode slurry on a positive electrode current collector, followed by drying and roll-pressing.
[0070] Optionally, the negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer covering the surface of the negative electrode current collector, and the negative electrode current collector can be the carbon-coated current collector provided in the first aspect;
[0071] The negative electrode active material layer includes a negative electrode binder, a negative electrode active material and a negative electrode conductive agent. The negative electrode binder includes but is not limited to polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene ethylene butylene styrene copolymer (SEBS), styrene butadiene styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, etc., and users can choose according to actual needs, and are not specifically limited here. The negative electrode active material includes but is not limited to graphite, soft carbon, hard carbon, silicon oxygen or silicon carbon, etc., and users can choose according to actual needs, and are not specifically limited here. The negative electrode conductive agent includes but is not limited to conductive carbon black, carbon nanotubes, vapor-grown carbon nanotubes or nano-carbon fibers, etc., and users can choose according to actual needs, and the present invention does not make specific limitations.
[0072] Alternatively, the main function of the separator is to separate the negative electrode from the positive electrode and provide a path for the movement of lithium ions. Any separator can be used without particular limitation, as long as it is a separator commonly used in secondary batteries. In particular, a separator with excellent electrolyte wettability and low resistance to ion movement in the electrolyte is preferred. Specifically, a porous polymer film can be used, for example, a porous polymer film made of polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure with more than two layers thereof. In addition, a typical porous non-woven fabric can be used, for example, a non-woven fabric formed of glass fiber, polyethylene terephthalate fiber, etc. having a high melting point. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single layer or multilayer structure.
[0073] Optionally, the present application does not specifically limit the type of electrolyte, and any known electrolyte material can be used in the present application without violating the inventive concept of the present application. As an illustrative example, the electrolyte can be a liquid electrolyte, a solid electrolyte, or a mixture of a solid electrolyte and a liquid electrolyte.
[0074] In addition, the electrolyte used in the present invention may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc. that can be used in the manufacture of a secondary battery, but is not limited thereto.
[0075] Specifically, the electrolyte may include an organic solvent and a lithium salt; any organic solvent may be used without particular limitation as long as it can function as a medium through which ions participating in an electrochemical reaction of a battery can move. Specifically, as the organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and E-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (wherein R is a linear, branched or cyclic C2-C20 hydrocarbon group, and may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or cyclopentane sulfone; any compound can be used as the lithium salt without particular limitation as long as it can provide the lithium ions used in the lithium secondary battery. Specifically, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, etc. may be used as the lithium salt.
[0076] Further, the electrolyte may be a solid electrolyte, and the solid electrolyte particles may contain one or more polymer components, oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, borate solid electrolytes, nitride solid electrolytes or hydride solid electrolytes.
[0077] Example 1
[0078] This embodiment provides a carbon-coated current collector, which includes a current collector substrate (8 μm thick copper foil) and carbon-coated layers on both sides of the current collector substrate, wherein the carbon-coated layers on each side include a conductive agent, a binder and a cross-linking agent;
[0079] The conductive agent is conductive carbon black (Super P, Termeco, Switzerland), and the binder includes polyacrylic acid (PAA, CAS No. 9003-01-4, solid content 15%) and polystyrene microspheres (PS, item No. ZKKY-8-0500, particle size D90 ranges from 4 to 5 μm, molecular weight is 12800);
[0080] The cross-linking agent is polycarbodiimide (CAS No.: 151-51-9);
[0081] The mass ratio of the PAA, PS microspheres and cross-linking agent is 100:25:2.
[0082] The preparation method of the carbon-coated current collector is as follows:
[0083] The binder and the conductive agent were mixed in a mass ratio of 3:7, dissolved in water in this ratio, stirred evenly, and finally an aziridine crosslinking agent (the mass ratio of PAA, PS microspheres and crosslinking agent was 100:25:2) was added to prepare a carbon coating slurry with a solid content of 10%;
[0084] The carbon coating slurry was coated on both sides of the copper foil at a coating speed of 45 m / min and dried at 120°C to obtain a single-layer coating with a surface density of 0.5 g / m 2 of carbon-coated current collector.
[0085] Example 2
[0086] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass ratio of PAA, PS microspheres and cross-linking agent is 100:25:1.
[0087] The rest of the preparation methods and parameters were the same as those in Example 1.
[0088] Example 3
[0089] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass ratio of PAA, PS microspheres and cross-linking agent is 100:25:3.
[0090] The rest of the preparation methods and parameters were the same as those in Example 1.
[0091] Example 4
[0092] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass ratio of PAA, PS microspheres and cross-linking agent is 100:25:4.
[0093] The rest of the preparation methods and parameters were the same as those in Example 1.
[0094] Example 5
[0095] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass ratio of PAA, PS microspheres and cross-linking agent is 100:15:2.
[0096] The rest of the preparation methods and parameters were the same as those in Example 1.
[0097] Example 6
[0098] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass ratio of PAA, PS microspheres and cross-linking agent is 100:30:2.
[0099] The rest of the preparation methods and parameters were the same as those in Example 1.
[0100] Example 7
[0101] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass ratio of PAA, PS microspheres and cross-linking agent is 100:35:2.
[0102] The rest of the preparation methods and parameters were the same as those in Example 1.
[0103] Example 8
[0104] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass ratio of PAA, PS microspheres and cross-linking agent is 100:10:2.
[0105] The rest of the preparation methods and parameters were the same as those in Example 1.
[0106] Example 9
[0107] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass ratio of PAA, PS microspheres and cross-linking agent is 100:40:2.
[0108] The rest of the preparation methods and parameters were the same as those in Example 1.
[0109] Example 10
[0110] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass ratio of PAA, PS microspheres and cross-linking agent is 100:25:5.
[0111] The rest of the preparation methods and parameters were the same as those in Example 1.
[0112] Embodiment 11
[0113] The difference between this embodiment and embodiment 1 is that the particle size D90 of the PS microspheres in this embodiment is in the range of 2 to 3 μm.
[0114] The rest of the preparation methods and parameters were the same as those in Example 1.
[0115] Example 12
[0116] The difference between this embodiment and embodiment 1 is that the particle size D90 of the PS microspheres in this embodiment is in the range of 3 to 4 μm.
[0117] The rest of the preparation methods and parameters were the same as those in Example 1.
[0118] Example 13
[0119] The difference between this embodiment and embodiment 1 is that the particle size D90 of the PS microspheres in this embodiment is in the range of 5 to 6 μm.
[0120] The rest of the preparation methods and parameters were the same as those in Example 1.
[0121] Embodiment 14
[0122] The difference between this embodiment and embodiment 1 is that the particle size D90 of the PS microspheres in this embodiment is in the range of 6 to 7 μm.
[0123] The rest of the preparation methods and parameters were the same as those in Example 1.
[0124] Embodiment 15
[0125] The difference between this embodiment and embodiment 1 is that the molecular weight of the PS microspheres in this embodiment is 6300.
[0126] The rest of the preparation methods and parameters were the same as those in Example 1.
[0127] Example 16
[0128] The difference between this embodiment and embodiment 1 is that the molecular weight of the PS microspheres in this embodiment is 35,000.
[0129] The rest of the preparation methods and parameters were the same as those in Example 1.
[0130] Embodiment 17
[0131] The difference between this embodiment and embodiment 1 is that the molecular weight of the PS microspheres in this embodiment is 70,000.
[0132] The rest of the preparation methods and parameters were the same as those in Example 1.
[0133] Embodiment 18
[0134] The difference between this embodiment and embodiment 1 is that the particle size D90 of the PS microspheres in this embodiment is in the range of 10 to 11 μm.
[0135] The rest of the preparation methods and parameters were the same as those in Example 1.
[0136] Embodiment 19
[0137] The difference between this embodiment and embodiment 1 is that the molecular weight of the PS microspheres in this embodiment is 5000.
[0138] The rest of the preparation methods and parameters were the same as those in Example 1.
[0139] Embodiment 20
[0140] The difference between this embodiment and embodiment 1 is that the molecular weight of the PS microspheres in this embodiment is 75,000.
[0141] The rest of the preparation methods and parameters were the same as those in Example 1.
[0142] Embodiment 21
[0143] The difference between this embodiment and embodiment 1 is that the current collector substrate in this embodiment is aluminum foil.
[0144] The rest of the preparation methods and parameters were the same as those in Example 1.
[0145] Comparative Example 1
[0146] The difference between this comparative example and Example 1 is that the binder provided in this comparative example does not contain PS microspheres.
[0147] The rest of the preparation methods and parameters were the same as those in Example 1.
[0148] Comparative Example 2
[0149] The difference between this comparative example and Example 1 is that the binder provided in this comparative example does not contain PAA.
[0150] The rest of the preparation methods and parameters were the same as those in Example 1.
[0151] Comparative Example 3
[0152] The difference between this comparative example and Example 1 is that this comparative example does not contain a cross-linking agent.
[0153] The rest of the preparation methods and parameters were the same as those in Example 1.
[0154] Comparative Example 4
[0155] The difference between this comparative example and Example 1 is that in this comparative example, PS microspheres are replaced by PS (CAS No. 9003-53-6).
[0156] The rest of the preparation methods and parameters were the same as those in Example 1.
[0157] Preparation of electrode sheets and preparation of batteries.
[0158] (1) The carbon-coated current collectors provided in Examples 1-20 and Comparative Examples 1-4 were used to prepare negative electrode sheets, and then a battery was prepared, as follows:
[0159] (a) The negative electrode active material is a silicon carbon material (Guangdong Kaijin), the binder is LA132 (Indile), and the conductive agent is Super P (Swiss Termeco); the active material: binder: conductive agent = 8:1:1 are stirred and mixed, and after mixing evenly, coated on both sides of the carbon-coated current collector provided in Example 1, and dried in a vacuum drying oven at 120° C. for 12 h to obtain the negative electrode plate;
[0160] (b) The button battery shell is of CR2032 model, the diaphragm is of 20um diaphragm (Φ19 PP microporous membrane Celgard2400), the electrolyte is a lithium battery basic electrolyte (i.e. EC and DEC are used as a mixed solvent in a volume ratio of 1:1, and 1.1 mol / L LiPF6 is added), the electrode is the negative electrode provided by Example 1-14 and Comparative Example 1-4, and the button battery is assembled in an argon-filled glove box in the following assembly order: battery shell - placing negative electrode - dripping electrolyte - placing diaphragm - dripping electrolyte - placing lithium sheet - placing gasket spring - battery shell.
[0161] (2) The carbon-coated current collector provided in Example 21 is used to prepare a positive electrode sheet, and then a battery is prepared, and the process is as follows:
[0162] (a) The positive electrode active material is LFP (Defang Nano DF5F), the binder is PVDF (Kureha, KF7200), and the conductive agent is Super P (Swiss Termeco); the active material: binder: conductive agent = 95:2:3 are stirred and mixed, and after mixing evenly, coated on a carbon-coated copper foil, and dried in a vacuum drying oven at 120°C for 12h to obtain a positive electrode sheet;
[0163] (b) The button battery shell is of CR2032 model, the diaphragm is of 20um diaphragm (Φ19 PP microporous membrane Celgard2400), the electrolyte is a lithium battery basic electrolyte (i.e. EC and DEC are used as a mixed solvent in a volume ratio of 1:1, and 1.1 mol / L LiPF6 is added), the electrode is the positive electrode provided in the embodiment and the comparative example, and the button battery is assembled in an argon-filled glove box in the following assembly order: battery shell - placing the positive electrode - dripping the electrolyte - placing the diaphragm - dripping the electrolyte - placing the lithium sheet - placing the gasket spring - battery shell.
[0164] Performance Test:
[0165] The carbon-coated current collectors provided in Examples 1-20 and Comparative Examples 1-4 were subjected to a penetration resistance test. The test conditions were as follows: a sample of 3 cm*3 cm in size was cut and placed on the test point of the penetration resistance meter. The equipment was started and the test was started. The test area was 180 mm 2 , the test pressure is 4000N, the test time is 20s, after the test time, read the data, the test results are shown in Table 1;
[0166] The electrode sheets provided in Examples 1-21 and Comparative Examples 1-4 were subjected to a sheet peeling force test. The test conditions were as follows: a sample of 10 cm*4 cm in size was cut and fixed on a steel plate. The steel plate and the sample were fixed in the sample test area of the peeling force tester. The speed was set to 200 mm / min, the test distance was 200 mm, the equipment was started, and after the test was completed, the data was read. The test results are shown in Table 1.
[0167] The batteries provided in Examples 1-20 and Comparative Examples 1-4 were subjected to performance tests. A button battery charge and discharge tester (Wuhan Blue Electric, CT2001A) was used to perform charge and discharge tests on the button batteries. The voltage range was 2.7-4.2V and the current was 0.2C. The test results are shown in Table 2.
[0168] The battery provided in Example 21 was subjected to a performance test under the following test conditions: voltage range was 2.0-3.6V, current was 0.2C, and the test results are shown in Table 3.
[0169] Table 1
[0170]
[0171]
[0172] Table 2
[0173]
[0174]
[0175] Table 3
[0176] First charge and discharge efficiency (%) Embodiment 21 89.7
[0177] From Table 1 to Table 3, we can get:
[0178] From the data results of Examples 1-7, Examples 11-17 and Example 21, it can be seen that the carbon-coated current collector provided by the present invention can be a positive electrode current collector or a negative electrode current collector. The polyacrylic acid polymer and the polystyrene (PS) microspheres are synergistically cross-linked by a cross-linking agent to further regulate the corresponding mass ratio, the molecular weight of the PS microspheres and the range of D90, thereby improving the bonding effect between the carbon-coated layer and the electrode active material layer, reducing the internal resistance of the battery, greatly improving the initial charge and discharge efficiency of the battery, and reducing the interface resistance;
[0179] From the data results of Examples 1-10, it can be seen that by further adjusting the mass ratio of the polyacrylic acid polymer, the polystyrene microspheres and the cross-linking agent to 100:(15-35):(1-4), the electrode peeling force can be better improved, the penetration resistance can be reduced, and the battery performance can be improved;
[0180] From the data results of Example 1 and Examples 11-20, it can be seen that after further adjusting the D90 of the polystyrene microspheres to 1-9 μm and the molecular weight of the polystyrene microspheres to 6000-70000, the internal resistance is reduced to the maximum extent, and the initial charge and discharge efficiency of the battery end is improved; at the same time, the bonding effect of the carbon coating layer is more excellent;
[0181] From the data results of Example 1 and Comparative Examples 1-4, it can be seen that the carbon-coated current collector structure provided by the present invention, the polyacrylic acid polymer, polystyrene (PS) microspheres, and the cross-linking agent must cooperate with each other to achieve the purpose of current collector adhesion, reduce internal resistance, and improve battery performance.
[0182] In summary, the carbon-coated current collector provided by the present invention, the polyacrylic acid polymer and the polystyrene (PS) microspheres improve the bonding effect between the carbon-coated layer and the electrode active material layer through the action of a cross-linking agent. At the same time, the spherical structure of PS allows the normal transmission of lithium ions during battery operation, reduces the internal resistance of the battery, and greatly improves the initial charge and discharge efficiency of the battery. The two-dimensional bonding network structure formed by the polyacrylic acid polymer and the polystyrene microspheres through the action of a cross-linking agent is more compact, thereby better reducing the interface resistance.
[0183] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A carbon-coated current collector, characterized in that: The carbon-coated current collector comprises a current collector substrate and a carbon-coated layer on at least one side of the current collector substrate; the carbon-coated layer comprises a conductive agent, a binder and a cross-linking agent; the binder comprises a polyacrylic acid polymer and polystyrene microspheres.
2. The carbon-coated current collector according to claim 1, characterized in that: The mass ratio of the conductive agent to the binder is 1:2 to 3:8; The mass ratio of the polyacrylic acid polymer, the polystyrene microspheres and the cross-linking agent is 100:(15-35):(1-4); The crosslinking agent includes any one of aziridine, polycarbodiimide or polyisocyanate, or a combination of at least two of them.
3. The carbon-coated current collector according to claim 1, characterized in that: The ratio of the particle size D90 of the polystyrene microspheres to the molecular weight of the polystyrene microspheres is 1 / 70000 to 9 / 6000, and the unit of D90 is μm.
4. The carbon-coated current collector according to claim 1, characterized in that: The particle size D90 of the polystyrene microspheres is 1 to 9 μm.
5. The carbon-coated current collector according to claim 1, characterized in that: The molecular weight of the polystyrene microspheres is 6,000 to 70,000.
6. A method for preparing a carbon-coated current collector according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Mixing a conductive agent, a binder, a cross-linking agent and a solvent to obtain a carbon-coated layer slurry, and applying the carbon-coated layer slurry to at least one side of the current collector substrate to obtain the carbon-coated current collector; Wherein, the binder comprises polyacrylic acid polymer and polystyrene microspheres.
7. The method for preparing a carbon-coated current collector according to claim 6, characterized in that: After the coating is completed, the carbon-coated current collector is obtained by drying.
8. An electrode plate, characterized in that: The electrode plate comprises the carbon-coated current collector according to any one of claims 1 to 5 and an electrode active material layer located on at least one side of the carbon-coated current collector; the electrode active material layer comprises a positive electrode active material layer or a negative electrode active material layer.
9. The electrode plate according to claim 8, characterized in that: The electrode active material layer is a negative electrode active material layer.
10. A battery, characterized in that: The battery comprises the electrode sheet as claimed in claim 8 or 9.
Citation Information
Patent Citations
Machine for threading bolts
CA40155A
Current collector microstructure preparation system and method based on lithium battery pole piece
CN111430719A
Lithium ion battery current collector conductive coating, lithium ion battery current collector, pole piece and lithium ion battery
CN111710871A
Cited By
Carbon-coated slurry, carbon-coated copper foil, negative plate and lithium ion battery
CN120718536A
Composite current collector and preparation method thereof, battery electrode and sodium ion battery
CN120834212A
Composite current collector, method for preparing the same, battery electrode and sodium ion battery
CN120834212B
Carbon-coated slurry, carbon-coated current collector, negative plate and battery
CN121306637A